Pemanfaatan Aplikasi Google Maps sebagai Bentuk Digitalisasi Pemasaran pada UMKM Warkop di Desa Pepelegi Sidoarjo - Ernawati Ernawati; M Najib Zakariya; Moh Riski (Lembaga Pengembangan Kinerja Dosen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic contribution to economic equality and job creation, especially in rural areas. However, limitations in mastering digital technology, especially in marketing, are still a major challenge for MSMEs in Pepelegi Village, Sidoarjo. This community service activity aims to increase the digitalization capacity of MSMEs through training and mentoring in utilizing Google Maps as a promotional media. The method used in this study is Participatory Action Research (PAR), which includes observation, interviews, training, and evaluation. The location of the activity focused on the MSME Warkop Pojok SR in Pepelegi Village, involving the active participation of local business actors. The results of the activity showed an increase in participants' knowledge and skills in creating and managing business profiles on Google Maps. This has a positive impact on business visibility and the potential for increasing income. Digitalization through Google Maps not only makes it easier for consumers to find business locations, but also provides information regarding operating hours, customer reviews, and business contacts. Thus, this activity is expected to be a model for empowering MSMEs based on digital technology that can be replicated in other areas. The sustainability of the program can be strengthened through cross-sector collaboration to support the acceleration of MSME digital transformation.